A Case of Postpartum Seizures Following Spinal Anesthesia and Epidural Blood Pach - Doğan, Rafi; Horasanlı, Bahriye; Özçimen, Emel Ebru; Başaran, Betül; Kaya, Yavuz (Gynecology Obstetrics & Reproductive Medicine, 2011)
A 29- year old healthy female who developed seizures on post-partum period after cesarean section under spinal anasthesia and epidural blood pach is discussed and the causes of the post-partum esizures associated with post-dural punctured headache after spinal and epidural interventions are investigated. All of the causes for post-partum seizure were excluded. There was no evidence of pre-eclampsia antepartum or post-partum. All clinical investigations were normal including electro encephalography, computerised tomography and magnetic resonance imaging angiography. All symptoms resolved completely. The aetiology of the seizures was discussed based on cerebral artery vasospasm and the increase of the intracranial pressure maybe an aetiological factor.